2006
DOI: 10.1080/02713680600899887
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure and Ocular Pulse Amplitude Comparisons in Different Types of Glaucoma Using Dynamic Contour Tonometry

Abstract: DCT measures an IOP that is significantly higher than GAT IOP in glaucoma and control subjects but not in ocular hypertensives. Furthermore, the DCT may measure an IOP that is independent of the CCT, which may not be true for the GAT, which increases with the CCT. OPA was highest in OHT and may be affected by the IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 22 publications
8
57
3
2
Order By: Relevance
“…Although subjects with variable lens change no matter what the acquired or senile conditions are, a clinician could consider using GAT or Tono-Pen to measure IOP. Some studies have reported a positive association between IOP and OPA 5,7,15,27 In this study, OPA correlated positively with GAT and Tono-Pen readings, but was not significantly associated with NCT or DCT. Further, larger OPA was negatively correlated with the differences between DCT and GAT readings and between NCT and GAT readings.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although subjects with variable lens change no matter what the acquired or senile conditions are, a clinician could consider using GAT or Tono-Pen to measure IOP. Some studies have reported a positive association between IOP and OPA 5,7,15,27 In this study, OPA correlated positively with GAT and Tono-Pen readings, but was not significantly associated with NCT or DCT. Further, larger OPA was negatively correlated with the differences between DCT and GAT readings and between NCT and GAT readings.…”
Section: Discussionmentioning
confidence: 61%
“…Regarding CCT, IOP readings using applanation tonometers usually increase with thicker CCT. 6,9,10,12 Previous reports have proposed various CCT-based correction formulas for GAT; 15,16 however, some studies suggested that the nonlinear correlation between GAT readings and CCT precludes a simple correction formula. [17][18][19] In some cases, the magnitude of change in IOP might be disproportional to ablation depth after refractive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…27 This study found no proportional bias between the GAT and DCT readings. There are varied results in the literature for proportional bias; some studies have, like us, found no bias between DCT and GAT measurement, 25,28 others have found increasing differences between DCT and GAT as IOP increased, 29,30 or decreasing differences in another. 31 DCT values for IOP are similar to intracameral manometric IOP in vivo 32 and are more similar than GAT (which are significantly lower) in cadaveric eyes.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results, in spite of different study populations, have been reported by previous investigations. 39,40 Moreover, we evaluated the performance of DCT over a wide range of CCT and IOP values recorded in our study population. The DIOP between DCT and GAT measurements decreased with an increase in CCT (Figures 2 and 3) and IOP values (Figure 4).…”
Section: Discussionmentioning
confidence: 99%